Learning through Facebook and YouTube: Perceptions of Students of University of Dhaka (Teacher’s World: Journal of Education and Research, 2024)
In an age of globalization, social networking sites are integral to student life as in Bangladesh as well as globally. Among others, Facebook and YouTube are the most popular and widely utilized social networking platforms among Bangladeshi students. This article examines how students at the University of Dhaka, Bangladesh use social networking sites (such as Facebook and YouTube) for their formal and informal studies. Following mixed methodology, data collection was completed using a structured survey questionnaire and a few semi-structured interviews. Social Learning Theory (SLT) is relevant for this research since social networking sites such as Facebook, YouTube, etc., have contributed to education through observation, imitation and modeling. Attending online classes, communicating with class teachers and classmates, collecting information about the class and exam schedules, uploading, downloading, and sharing academic materials, participating in group discussions, downloading tutorial videos of educational courses and informal education topics, and completing online coursework have come forth as the most prevalent uses of Facebook and YouTube by University of Dhaka students during their studies.Teacher’s World: Journal of Education and Res arch, 50(1): 95-118